Complete structural characterisation of the mammalian and Drosophila TRAF genes: implications for TRAF evolution and the role of RING finger splice variants. - Grech, A.; Quinn, R.; Srinivasan, D.; Badoux, X.; Brink, R. (Molecular Immunology, 2000)
The complete murine TRAF2 gene was obtained using a lambda phage and PCR cloning strategy. The gene was found to consist of ten coding and one 5' non-coding exon spread over 28 kbp of DNA. We also report the basic structure of the human TRAF5 and TRAF6 genes obtained by analysis of the genomic DNA database. Comparison of these three gene structures, along with those previously described for TRAF1, TRAF3 and TRAF4, revealed the evolutionary relationship between the six known mammalian TRAFs. The TRAF1/TRAF2 and TRAF3/TRAF5 gene pairs were found to have arisen from recent independent gene duplications and to share a common ancestral gene. Specific TRAF4 and TRAF6 precursor genes were found to have arisen earlier during evolution, with the divergence of the TRAF6 precursor occuring earliest of all. The Drosophila genome was found to contain three TRAF family genes: dTRAF1, dTRAF6 (dTRAF2) and a previously undescribed member we have designated dTRAF3. TRAF-C domain homology indicated that dTRAF3 is likely to have derived from the common precursor for the TRAF 1, 2, 3 and 5 genes, whilst dTRAF1 and dTRAF6 have derived from the TRAF4 and TRAF6 precursor genes, respectively. The implication of these results for the functional evolution of TRAFs is discussed. Analysis is also presented of the conservation of the TRAF2A molecule, a TRAF2 alternate splice isoform with an extended RING finger domain previously described in mice. TRAF2A was not found to be encoded by the human or rat TRAF2 genes and no other murine TRAF gene was found to produce a similar alternate splice product. We also report that the sequence of murine C57BL/6 TRAF4 differs significantly from the published murine TRAF4 sequence, but appears to represent the actual TRAF4 sequence expressed in many mouse strains.